1982
DOI: 10.1051/rphysap:01982001706037300
|View full text |Cite
|
Sign up to set email alerts
|

Castaing microprobe analysis of doped polyacetylene films

Abstract: 2014 Le dopage a permis de modifier considérablement les propriétés électriques du polyacétylène, et a été le point de départ de l'intérêt considérable porté à ce matériau depuis quelques années. Ce court article met en évidence l'existence d'un dopage inhomogène observé avec les dopants I2 et SbF5. Il montre en conséquence les risques d'erreur que ces inhomogénéités peuvent introduire lors de l'interprétation de certaines mesures physiques. Abstract 2014 By doping, the electrical behaviour of polyacetylene fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moses et al [34] have shown the importance of macroscopic nonuniform doping on physical properties. Nonuniform doping has also been studied by Rolland [31], Janossy [33], Epstein [35], Montaner [12]. The origin of the concentration gradients through the films, has been discussed by Benoit et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…Moses et al [34] have shown the importance of macroscopic nonuniform doping on physical properties. Nonuniform doping has also been studied by Rolland [31], Janossy [33], Epstein [35], Montaner [12]. The origin of the concentration gradients through the films, has been discussed by Benoit et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion of the iodine into the polymer can be evaluated, since the change in frequency during iodine doping is proportional to the change in mass. The diffusion of gases into polymers has been extensively studied. Crank and Park and many others use the sorption of vapors in polymers to determine the diffusion coefficient, D . Assuming D is constant and that diffusion is into a plane sheet, the relationship can be expressed as 34 where M t is the total amount of vapor absorbed at time t , M ∞ is the equilibrium sorption, l is the thickness of the sample, and m is an integer.…”
Section: Resultsmentioning
confidence: 99%
“…Various dopant species were used to obtain the metallic polymer, for example I2, MoCls. The morphology depends strongly of the dopant specie and the doping process [6].…”
mentioning
confidence: 99%